The Use of Infographics As A Representation Medium to Support Students’ Understanding in Physics Learning: A Literature Review - Laela, Oktavia; Dixit, Aparna (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Physics learning is often perceived as challenging by students due to its abundance of abstract concepts and quantitative explanations. One strategy that can help facilitate understanding is the use of infographics as a visual representation medium. This study aims to identify and analyze the role of infographics in enhancing students’ comprehension of physics concepts, while also exploring their potential and challenges in secondary school settings. The method employed is a literature review of seven relevant scientific articles discussing the use of infographics in the context of physics education. The analysis was conducted by examining the key findings of each article and categorizing them based on indicators of learning benefits. The findings reveal that infographics can increase students’ learning interest, engagement, and academic performance, both in cognitive and affective domains. Furthermore, infographics are effective in fostering students’ creativity through the implementation of project-based learning models and problem-based approaches. Identified challenges include teachers’ limited skills in designing effective infographics and the availability of supporting resources. Overall, the use of infographics holds significant potential as an innovative strategy to visually represent scientific information and improve the quality of physics learning in secondary schools.